Relationship Interests, Motivation and Attention Parents of Biology Student Learning Outcomes Race: Passage of Interest in SMA Negeri Percut Sei Tuan - Laina Zuhra; Melva Silitonga; Mufti Subdibyo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine: (1) Biology learning outcomes of students; (2) Student interest in learning; (3) student motivation; (4) Parents' attention; (5) The relationship between interest, motivation and parental attention to student biology learning outcomes in the cross-interest group of class X students. This research was conducted at SMA Negeri 2 Percut Sei Tuan in 2019. The research method is a descriptive correlational research method with a research sample of 100 students. determined by cluster random sampling (random sample class). The research instrument consisted of a cognitive learning outcome test, a student interest questionnaire, a student learning motivation questionnaire, and a student parent attention questionnaire that had been tested for validity, reliability, discrepancy and level of difficulty. Data were analyzed using correlation analysis techniques using SPSS 21.0 for windows. The results showed: (1) Cognitive learning outcomes of 74.08 which fall into the moderate category; (2) The level of student interest was 64.67 which was in the medium category; (3) The level of student motivation is 68.46 which belongs to the medium category; (4) The level of attention of the students' parents is 66.74 which is in the moderate category; (5) The significant relationship between student interest in learning, student motivation, and parents' attention to student cognitive learning outcomes with Sig 0.00 <0.05.